Anas Family Model Pada Level Individu dalam Pengendalian Stunting di Wilayah Puskesmas Lima Puluh - Riski Novera Yenita; Rifa Yanti; Jufenti Ade Fitri (Jurnal Zona, 2024)
One of the government's current focus is stunting prevention. This effort aims to ensure that Indonesian children can grow and develop optimally and to the maximum, accompanied by emotional, social, and physical skills that are ready to learn, as well as being able to innovate and compete at a global level. According to the Gizi Status Survey Report of Balita Indonesia (SSGBI) Based on stunting data of Pekanbaru city, the highest percentage of stunting cases are in the Fifty district of 42 cases. The type of research used is quantitative with the type of cross sectional study design. The sample in this study was 42 respondents. Data analysis is done univariately. The results of the study showed that out of 42 respondents obtained results on the parental education variable were 25 respondents (59.5%). In the attitude variable was enough 30 respondents (71.4%). Behavior was enough as much as 32 respondants (76.2%), In the sanitation variable, the majority were sanitation eligible as many respondents 17 (56.7%). It is recommended that Puskesmas Fifty Cities Pekanbaru be a source of information to the perpetrators and develop health promotion about patterns of parental care and maintain good sanitation of the environment against stunting incidents Information to the stunt party and developing health promotion on parental care patterns andining good sanitation of the environment against stunting incidents as one of the guidelines for changing behavior even better.